KONSEP HUKUM ZAKAT SEBAGAI INSTRUMEN DALAM MENINGKATKAN PEREKONOMIAN UMMAT - NAIMAH, NAIMAH (Syariah: Jurnal Hukum dan Pemikiran, 2014)
Zakat is charity of worship and included in the five pillars of Islam, because zakat is the foundation of Islam, in addition to an absolute obligation for a Muslim. It is also fully aware that the charity is a key instrument in growing the economy and improving the distribution tool. Then during the practice of Prophet Muhammad Saw in the compulsory zakat in times of Apostle in Medina, where nishab is set up, and stats is responsible in managing. This study explores how the concept of charity law as an instrument to improve the economy ummah, how positive law in Indonesia, which was formed to be able to institutionalize zakat order to function optimally, huge potential utilization of zakat can be achieved. The findings showed that generally, the presence of act No. 23 of 2011 on the management of zakat was instrumental in the development of the organization or institution of zakat in Indonesia, because the act provides legal certainty for the operational organization of zakat (OPZ), and increased public awareness in regular charity through zakat institution or organization zakat (OPZ). In addition, this act provides the foundation for the implementation of the concept of zakat productive.This law can be important instrument to achieve the goal of zakat as the remover of poverty, reduce unemployment and improve the ummahs economy.